Majówki i wycieczki szkolne jako forma pracy dydaktyczno-wychowawczej na łamach lwowskiej „Szkoły” okresu zaborów - Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2023)
The aim of the article is to present the debate on the teaching and educational effectiveness of school trips, described in Lviv “Szkoła”, the oldest Galician educational magazine –, from the moment the periodical was founded in 1868 until Poland regained independence. In the pages of this magazine, the leading representatives of the teaching community of the time, often professionally active teachers, expressed their opinions on the subject, analysing both the possibilities and the risks related to a broader use of these forms of teaching work. They often put forward original proposals regarding formal issues of the organisation of trips and outings, also referring to their own experiences in this area. The debate was not free from polemics but a majority of its participants positively assessed trips as a means of physical, health, hygienic and aesthetic education of students. The trips were also recognised to be a perfect opportunity to conduct illustrative geography or history lessons, and to shape civic and patriotic attitudes.